2011
DOI: 10.1080/13506285.2011.618151
|View full text |Cite
|
Sign up to set email alerts
|

Changing the focus of attention: The interacting effect of valence and arousal

Abstract: We examined how valence and arousal of an image influence visual attention. ''Spotlight of attention'' theory suggests that positive affect broadens, and negative affect narrows, one's aperture of attention, whereas the arousal theory literature suggests that arousal level is what modulates attentional focus, with highly arousing affect capturing attention, regardless of valence. In two experiments, a digit parity task was used to index the influence of valence, and arousal, on visual attention. Positive or ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
41
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 41 publications
4
41
1
Order By: Relevance
“…Indeed, apart from the research on time perception, a number of findings have indicated an interaction of arousal and attention. Several researchers have reported variations in the allocation of visual attention due to induced differences in arousal (De Houwer & Tibboel, 2010;Fernandes, Koji, Dixon, & Aquino, 2011;McConnell & Shore, 2010;Verbruggen & De Houwer, 2007). However, the question is now whether we can determine whether increased arousal or a stronger focus on timing caused the differences in time perception that we obtained.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Indeed, apart from the research on time perception, a number of findings have indicated an interaction of arousal and attention. Several researchers have reported variations in the allocation of visual attention due to induced differences in arousal (De Houwer & Tibboel, 2010;Fernandes, Koji, Dixon, & Aquino, 2011;McConnell & Shore, 2010;Verbruggen & De Houwer, 2007). However, the question is now whether we can determine whether increased arousal or a stronger focus on timing caused the differences in time perception that we obtained.…”
Section: Discussionmentioning
confidence: 71%
“…Of course, this is only a first speculation about the relationship between attention and arousal within the timing process. Given previous findings about the impact of arousal on attention (De Houwer & Tibboel, 2010;Fernandes et al, 2011;McConnell & Shore, 2010;Verbruggen & De Houwer, 2007), and vice versa (De Bourdeaudhuij, Crombez, Deforche, Vinaimont, Debode and Bouckaert 2002), it could be worthwhile to take a closer look at this topic in the context of time perception.…”
Section: Discussionmentioning
confidence: 99%
“…When the attentional focus is broad, however, the area of visual cortex showing enhanced activity is of greater extent, but the degree of enhancement is attenuated (Müller, Bartelt, Donner, Villringer, & Brandt, 2003; also Chen, Marshall, Weidner, & Fink, 2009). Although some factors that trigger attentional focusing have been identified -mood, for instance, causes the focus of attention to expand or contract (Fernandes, Koji, Dixon, & Aquino, 2011; Friedman & Förster, 2010;Rowe, Hirsh, & Anderson, 2007) -relatively little is known about the many stimulus factors that might modulate the breadth of attention.…”
Section: Attending To Perceived Sizementioning
confidence: 99%
“…When the attentional focus is broad, however, the area of visual cortex showing enhanced activity is of greater extent, but the degree of enhancement is attenuated (Müller, Bartelt, Donner, Villringer, & Brandt, 2003; also Chen, Marshall, Weidner, & Fink, 2009). Although some factors that trigger attentional focusing have been identified -mood, for instance, causes the focus of attention to expand or contract (Fernandes, Koji, Dixon, & Aquino, 2011; Friedman & Förster, 2010;Rowe, Hirsh, & Anderson, 2007) -relatively little is known about the many stimulus factors that might modulate the breadth of attention.Of particular importance, it is not known how object representations guide attentional focusing.Objects are essential determinants of the deployment of attention (e.g., Egly, Driver, & Rafal, 1994;Tipper, Driver, & Weaver, 1991;Scholl & Pylyshyn, 1999;Serences, Schwarzbach, Courtney, Golay, & Yantis, 2004), and are represented at multiple levels of visual processing. Low-level representations code the primitive visual features of an object, such as brightness and edge orientation, Attending to Perceived Size 5 at the earliest stages of visual processing (e.g., Marr, 1982).…”
mentioning
confidence: 99%
“…As anger is typically a negative emotion and is highly motivational, our results are consistent with both perspectives and do not provide elucidation on this point. Moreover, the level of emotional arousal and age of the participants could also affect the outcome (Fernandes, Koji, Dixon, & Aquino, 2011;Noh, Larcom, Liu, & Isaacowitz, 2012). Future researchers should include these variables and, most importantly, compare anger with other emotions.…”
Section: Limitations and Directions For Future Researchmentioning
confidence: 99%